A new frequency domain composite adaptive filter - Nakanishi, I.; Itoh, Y.; Fukui, Y. (1997 IEEE International Symposium on Circuits and Systems, 2002)
This paper presents a new frequency domain adaptive filter with a composite adaptive algorithm. The proposed adaptive filter is based on the FIR filters, so that the continuous output signal can be obtained with stable convergence and no accumulated error. The proposed composite algorithm improves the convergence speed of the frequency domain adaptive filter keeping the fast convergence. The advantages of the proposed method are confirmed through the computer simulations in the adaptive line enhancer.